Picture this: Social distance and the mistreatment of migrant workers - Toman Barsbai; Vojtěch Bartoš; Victoria S. Licuanan; Andreas Steinmayr; Erwin R. Tiongson; Dean Yang (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
International migrant workers are vulnerable to abuses by their employers. We implemented a randomized controlled trial of an intervention to reduce mistreatment of Filipino women working as domestic workers (DWs) by their household employers in Hong Kong and Saudi Arabia. The intervention - encouraging DWs to show their employers a photo of their family while providing a small gift when starting employment - caused DWs to experience less mistreatment, have higher satisfaction with the employer, and be more likely to stay with the employer. DWs' families in the Philippines also come to view international labor migration more positively, while they generally remain unaware of the intervention. An online experiment with potential employers in Hong Kong and the Middle East suggests that a mechanism behind the treatment effect is a reduction in the employer's perceived social distance from the employee. A simple intervention can thus help to protect migrant workers without requiring public policy changes in the destination country.
Keywords: D9; J61; 330; temporary labor migration; working conditions; contract enforcement; dictator game